Evaluation of Pain Syndrome Treatment in Patients with Temporomandibular Joint Muscle Dysfunction Based on the Functional State of Masticatory Muscles - Zhehulovych З. Є.; Bezkorovaina Л. П. (Actual Dentistry, 2024)
Actuality. Treatment of temporomandibular joint dysfunction is an interdisciplinary problem that includes an interdisciplinary, complex simultaneous approach to eliminate the factors that cause the development of a dysfunctional state of the temporomandibular joint. Objective. To study the dynamics of changes in the functional state of masticatory muscles and pain syndrome against the background of orthopedic treatment with a modified occlusive splint in the case of temporomandibular joint (TMJ) musculoskeletal dysfunction. Materials and Methods. Among the examined persons (421 persons), 85 patients were randomly selected for analysis: 63 (74%) women and 22 (26%) men with TMJ MSD. Mean age of patients M±SD 36.2±10.8 years. The determined population was divided into three groups according to the diagnostic criteria of temporomandibular disorders. Group I included 8 (10%) patients with disc disorders, group II — 30 (35%) patients with myalgias, group III — 47 (55%) patients with combined pathology (disc disorders and myalgias). The pain syndrome was evaluated using the visual analog scale (VAS) before and after treatment, the symptoms of physical pain and manifestations of temporomandibular joint dysfunction were studied according to the results of the questionnaire. The functional state of the muscles was studied based on the results of electromyography. The statistical evaluation of the research results was carried out by analysis of variance (ANOVA) and non-parametric Kruskel-Wallis and Mann-Whitney tests. Results. Statistically, significant differences in the severity of the pain syndrome (p <0.05) were established in groups (Gr.I, Gr.II, Gr.III: MeI=1.5 points, MeII=4.7 points, MeIII=4.3 points ). After treatment in each of the groups, the pain syndrome decreased and amounted to MeI = 0.7 points, MeII - 1.3 points and MeIII = 1.2 points in the absence of statistically significant differences between the indicators (p>0.05). The torque index (To % ) in observation groups before treatment was established: GrI — 10.02±5.21, GrII — 9.29±5.91 and GrIII — 8.03±3.2 without statistically significant differences between groups (р> 0.05). After treatment, changes in To% indicators were determined in all groups: GrI — 7.69±3.52, GrII — 6.15±3.51, GrIII — 5.31± 1.97 with statistically significant differences between groups (р< 0.01). Before treatment, the asymmetry index As % was determined in GrI — 11.32±5.18, in Gr II — 11.55±7.81 and in Gr III — 14.04±4.58 without statistically significant differences between groups (p> 0.05). After treatment, a decrease in As% was found in GrI — 5.7±3.47, in GrII — 6.54±3.47 and in GrIII — 11.54±3.72 with statistically significant differences between groups (р<0.01 ). Before treatment, the ATTIV % activity index was established in GrI — 9.13±5.15, in GrII — 16.82±7.75 and in GrIII — 15.54 5.02 without statistically significant differences between groups (р>0, 05). After treatment, wed a decrease in ATTIV % indicators was determined: GrI — 6.76±3.34, GrII — 10.33±4.34 and GrIII — 11.51±3.87 with statistically significant differences between groups (р<0.01) . Conclusions. The use of a modified occlusive splint effectively improves the functional state of masticatory muscles and reduces pain syndrome in patients with musculoskeletal dysfunction of the temporomandibular joint.